9b2-1=0

Add 1 to both sides of the equation.

9b2=1

Divide each term in 9b2=1 by 9.

9b29=19

Cancel the common factor of 9.

Cancel the common factor.

9b29=19

Divide b2 by 1.

b2=19

b2=19

b2=19

Take the square root of both sides of the equation to eliminate the exponent on the left side.

b=±19

Simplify the right side of the equation.

Rewrite 19 as 19.

b=±19

Any root of 1 is 1.

b=±19

Simplify the denominator.

Rewrite 9 as 32.

b=±132

Pull terms out from under the radical, assuming positive real numbers.

b=±13

b=±13

b=±13

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

b=13

Next, use the negative value of the ± to find the second solution.

b=-13

The complete solution is the result of both the positive and negative portions of the solution.

b=13,-13

b=13,-13

b=13,-13

Solve using the Square Root Property 9b^2-1=0